Kewenangan Kantor Pertanahan Kota Administrasi Jakarta Utara Dalam Menyelesaikan Sengketa Tanah Melalui Mediasi Berdasarkan Peraturan Menteri Agraria Dan Tata Ruang/ Kepala BPN Nomor 21 Tahun 2020 Tentang Penanganan Dan Penyelesaian Kasus Pertanahan - Mahardika, Kamila Dwi (Universitas Sultan Ageng Tirtayasa, 2023)
Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 21 of 2020 concerning Handling and Settlement of Land Cases states that the authority of the Land Office is to provide efforts to resolve land disputes by providing mediation for the parties to the dispute. Land disputes as a land problem in Indonesia which continue to occur every year because land is an asset that has high value for human life so it is necessary to increase land administration, one of which is by providing efforts to resolve land disputes in the form of mediation. The theory used is authority theory and alternative dispute resolution theory. the authority of the North Jakarta Administrative City Land Office in carrying out mediation has been carried out in accordance with the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 21 of 2020 by holding mediation in 67 cases out of 113 cases reported in the 2016-2020 period with 3 successful cases peace. The large number of cases mediated were due to supporting factors such as human resources having a history of legal education, a large number of human resources and having a special mediation room